Vitamin B6 in anxiety: sleep and immune function - Pertiwi, Lintang Mega; Fanani, Mohammad; Hikmayani, Nur Hafidha (BKM Public Health and Community Medicine, 2023)
Objective: This scoping review aims to explore the role of vitamin B6 in sleep duration and immune function in individuals with anxiety disorders. Methods: A search was conducted on scientific databases such as PubMed, Science Direct, and Google Scholar using the keywords "vitamin B6", "sleep", "immune system," and "anxiety disorders." Only articles published in Indonesian or English between 2017-2023 were included. Result: The findings of this review suggest that individuals with anxiety disorders experience shorter sleep duration and lower immune function compared to those without anxiety disorders. Previous studies have shown that short sleep duration can increase stress and inflammation in adolescents and adults. Vitamin B6 synthesizes neurotransmitters, which significantly regulate sleep and anxiety symptoms. Additionally, previous research has suggested that vitamin B6 plays a vital role in the immune system by reducing cytokine production and inflammation responses in many signaling pathways. Conclusion: This scoping review provides preliminary evidence of the association between vitamin B6, sleep duration, and immune function, particularly in individuals with anxiety disorders. Further research is required to elucidate the mechanisms involved in this relationship. The findings of this review can support further research on the potential benefits of vitamin B6 for sleep duration and immune function.